Edificio Yara proyecto de restauración y adecuación - López Jerónimo, María Teresa (Universidad Michoacana de San Nicolas de Hidalgo, 2017)
The present document contains an intervention project for a patrimonial building, the case study is an eighteenth-century room house called Edificio Yara, located in the historic center of the city of Morelia, Michoacán; which has been declared a World Heritage Site since 1991. The property is one of the few neighborhood houses that remain standing nowadays; these houses are built for the families of the then city of Valladolid, with better materials and constructive systems than in the founding of the city. It is immersed between three of the most important historical districts of the city: the San Francisco neighborhood, the San Jose neighborhood and the San Juan neighborhood. The restoration project plans to eliminate and reverse the deterioration that this building has suffered throughout its history due mainly to the abandonment and lack of interest of the owners to keep it in adequate conditions for its preservation. The actions are proposed in accordance with current and current criteria of restoration, with respect to the history of the property; it is also proposed a management plan to obtain the permits required for the intervention as well as a maintenance plan to avoid returning to the state of deterioration to which it has arrived. For this proposal of adequacy new uses are proposed that complement the use of services, they potentialize and in turn give the flexibility to the real estate not to depend on a single income to exercise the conservation plans. All of the above in order to preserve the identity of the city of Morelia and inherit our heritage to future generations who will be in charge of transmitting this historical document to their descendants and continue with this legacy.

El presente documento contiene un proyecto de intervención para un inmueble patrimonial, el caso de estudio es una casa habitación del siglo XVIII llamada Edificio Yara, ubicada en el centro histórico de la ciudad de Morelia, Michoacán; que cuenta con declaratoria de patrimonio de la humanidad desde 1991. El inmueble es una de las pocas casas de barrio que permanecen en pie hoy en día; estas casas se construyen para las familias de la entonces ciudad de Valladolid, con mejores materiales y sistemas constructivos que en la fundación de la ciudad. Se ubica inmersa entre tres de los barrios históricos más importantes de la ciudad: el barrio de San Francisco, el barrio de San José y el Barrio de San Juan. El proyecto de restauración tiene previsto eliminar y revertir los deterioros que este edificio ha sufrido a lo largo de su historia debido principalmente al abandono y falta de interés de los propietarios por conservarla en condiciones adecuadas para su preservación. Las acciones están propuestas en apego a los criterios actuales y vigentes de la restauración, con respeto hacia la historia del inmueble; se propone también un plan de gestión para la obtención de los permisos requeridos para la intervención así como un plan de mantenimiento que eviten regrese al estado de deterioro al que ha llegado. Para esta propuesta de adecuación se proponen nuevos usos que complementan el uso de servicios, lo potencializan y a su vez dan la flexibilidad al inmueble de no depender de un solo ingreso para ejercer los planes de conservación. Todo lo anterior con el fin de poder preservar la identidad de la ciudad de Morelia y heredar nuestro patrimonio a futuras generaciones que serán las encargadas de trasmitir este documento histórico a sus descendientes y continuar con este legado.
Facultad de Arquitectura. Especialidad en Restauración de Sitios y Monumentos
Keywords: info:eu-repo/classification/cti/4; FA-E-2017-0354; Casa; Conservación; Patrimonio; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3210